Pack Your Duds. (For San Francisco) - Joe Meyer::::::::: (Lyon Music Co.)
Piano and vocal score, 8 p. Score c1915 by Joe Meyer. Publishers (Les. Lorden Music Co., San Francisco) advertisement on verso of leaf.